Gender Equality Perspectives on Female Labor Force in West Bandung Regency - Subagja, Yayang Hendri (Mashadiruna Jurnal Ilmu Al-Qurân dan Tafsir, 2023)
Research conducted in West Bandung Regency, West Java, Indonesia, reveals that the challenges to achieving gender equality stem from differences in perspectives between men and women regarding rights, obligations, roles, and social status. One of these discussions often revolves around the issue of gender equality in the labor force, primarily concerning the rights and responsibilities guaranteed to Indonesian citizens by the 1945 Constitution. Gender equality in employment is both a governmental responsibility to protect citizens' rights and has cultural underpinnings. There still exist several institutional and socio-cultural barriers to improving gender equality in the workforce, including workers' awareness of their rights and the bargaining power of female employees. Therefore, it is believed that the government should play a crucial role in promoting gender equality by strengthening the enforcement of gender equality laws in the labor sector and enhancing labor market oversight. Furthermore, increasing awareness of gender equality among female workers and providing social protection for women in the informal sector is essential.